mNutrition Ghana Endline Study - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
mNutrition was a five-year global initiative supported by the Department for International Development (DFID) between 2013 and 2018, organized by GSMA, implemented by in-country mobile network operators and evaluated by researchers from GAMOS, the Institute of Development Studies (IDS) and the International Food Policy Research Institute (IFPRI), with the objective of building effective mobile phone-based advisory services for improving nutrition outcomes. In Ghana, mNutrition was implemented through the Vodafone Farmers Club (VFC) SMS program, and the service offered both agricultural and nutrition information through mobile voice and SMS services in addition to free calls between VFC members to improve the nutritional status of smallholder farmers’ households and to increase their agricultural productivity. To determine the causal effect of the program on dietary diversity and agricultural production, a cluster randomized encouragement design was employed to randomly expose treatment communities to promotional activities to sign up to VFC. Household interviews were conducted before and after the intervention. Quantitative data-collection took place in the Central Region and Upper West Region of Ghana. At baseline, 3933 households from 207 communities (104 treatment and 103 control) were interviewed. Of these 3933 households, 3802 households were interviewed at the endline. Interviews were conducted with both primary male and female members of the household.